2020
DOI: 10.1097/md.0000000000022745
|View full text |Cite
|
Sign up to set email alerts
|

A STROBE-compliant case–control study

Abstract: Topical atropine has become a mainstream treatment of myopia throughout East and Southeast Asia, but it is uncertain whether long-term topical atropine therapy induces intraocular pressure (IOP) elevation and subsequent development of glaucoma. We then prospectively examined the effects of long-term atropine treatment on IOP. Our case series collected 186 myopic children who were younger than 16 years of age. Complete ocular examination data, IOP and refractive status measurements beginning in 2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The clinical discussion revealed the relevant factors such as age, dosage, use time, etc., and whether the changes of IOP will be caused by atropine before and after its use [ 29 ]. At present, other literature has discussed the clinical effects or side effects of different doses of atropine [ 37 , 54 ]. The new significance of this study of atropine in myopic children is the use of the clinical data, combined with four artificial intelligence methods, to find out the reliable predictive value and the important rank of factors which may be related to topical atropine use for myopia control on intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical discussion revealed the relevant factors such as age, dosage, use time, etc., and whether the changes of IOP will be caused by atropine before and after its use [ 29 ]. At present, other literature has discussed the clinical effects or side effects of different doses of atropine [ 37 , 54 ]. The new significance of this study of atropine in myopic children is the use of the clinical data, combined with four artificial intelligence methods, to find out the reliable predictive value and the important rank of factors which may be related to topical atropine use for myopia control on intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may have been caused by a rebound effect since most of the study participants discontinued atropine treatment abruptly without tapering. Other publications on long-term effects of atropine indicate that the use of topical atropine eye drops does not lead to ocular hypertension and observed treatment effects are not correlated with the total cumulative dosage of atropine administered [ 124 ]. The effect of atropine (0.05% and 0.1%) has shown to last up to 4.5 years, with smaller rebound in long-term use [ 48 , 125 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a comparison of topical ocular drugs, atropine is generally considered to be well tolerated by the corneal epithelium: preparations of up to 1% were found to cause no epithelial damage [ 54 ]. A comparative analysis showed that there was no increase in eye pressure in the group of treated children [ 55 ]. BAC can exhibit toxic effects on the tear film and the corneal epithelium [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%